2021
DOI: 10.1111/cdev.13716
|View full text |Cite
|
Sign up to set email alerts
|

The representation of emotion knowledge across development

Abstract: The present study examined how children spontaneously represent facial cues associated with emotion. 106 three‐ to six‐year‐old children (48 male, 58 female; 9.4% Asian, 84.0% White, 6.6% more than one race) and 40 adults (10 male, 30 female; 10% Hispanic, 30% Asian, 2.5% Black, 57.5% White) were recruited from a Midwestern city (2019–2020), and sorted emotion cues in a spatial arrangement method that assesses emotion knowledge without reliance on emotion vocabulary. Using supervised and unsupervised analyses,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 104 publications
(103 reference statements)
0
11
0
Order By: Relevance
“…However, whether language shapes the development of dynamic features of emotions remains unknown. Valence is indeed a key dimension of how children perceive and think of emotion and emotion language (Bullock & Russell, 1984;Nook et al, 2017;Ponari et al, 2018Ponari et al, , 2020, but children's understanding of valence still shows protracted development over early childhood (Widen & Russell, 2003, 2008Woodard et al, 2022;Wu et al, 2022). If emotion language indeed supports children's developing emotion dynamics, we would predict that as children learn more emotion-related words, their emotion dynamics will more closely match those of adults.…”
mentioning
confidence: 96%
“…However, whether language shapes the development of dynamic features of emotions remains unknown. Valence is indeed a key dimension of how children perceive and think of emotion and emotion language (Bullock & Russell, 1984;Nook et al, 2017;Ponari et al, 2018Ponari et al, , 2020, but children's understanding of valence still shows protracted development over early childhood (Widen & Russell, 2003, 2008Woodard et al, 2022;Wu et al, 2022). If emotion language indeed supports children's developing emotion dynamics, we would predict that as children learn more emotion-related words, their emotion dynamics will more closely match those of adults.…”
mentioning
confidence: 96%
“…Most studies show that by age 5-6 years, most children accurately recognize and label static images of facial configurations on tasks similar to the one used here similarly to adults [39]. However, on the broader issue of how humans construe and understand emotions, there are significant changes in conceptual understanding between 6 year olds and adults [40]. The earlier research, using the same data that in this study, showed that for each year child became older, the odds of correctly identifying an emotion became 1.05 times larger [30].…”
Section: Discussionmentioning
confidence: 81%
“…Early childhood may be an especially important time for young children's development of valence‐based representations. Valence gradually emerges in the first 5 years of life as a dimension that organizes children's representations of nonlinguistic emotion cues and emotional experiences, in tandem with children's expanding vocabularies (Nencheva et al, 2021; Woodard et al, 2021). Children's ability to label emotions with specificity emerges during this same span in early childhood (Widen, 2013; Wu et al, 2022).…”
Section: Emotion Labels In Contextmentioning
confidence: 99%